2005
DOI: 10.1021/jp044556a
|View full text |Cite
|
Sign up to set email alerts
|

Biased Sampling of Nonequilibrium Trajectories:  Can Fast Switching Simulations Outperform Conventional Free Energy Calculation Methods?

Abstract: We have investigated the maximum computational efficiency of reversible work calculations that change control parameters in a finite amount of time. Because relevant nonequilibrium averages are slow to converge, a bias on the sampling of trajectories can be beneficial. Such a bias, however, can also be employed in conventional methods for computing reversible work, such as thermodynamic integration or umbrella sampling. We present numerical results for a simple one-dimensional model and for a Widom insertion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
202
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(204 citation statements)
references
References 36 publications
2
202
0
Order By: Relevance
“…The Jarzynski equality, on the other hand, can in principle be used to calculate the PMF. However it is well-known [12,13,14,15] that the exponential average in the Jarzynski equality depends crucially on a small fraction of realizations that transiently violate the second law of thermodynamics. Since such "magic" realizations are very unlikely to occur among a collection of fast rate realizations, it is clear that the potential of mean force cannot be determined accurately by the direct application of the Jarzynski equality.…”
Section: Introductionmentioning
confidence: 99%
“…The Jarzynski equality, on the other hand, can in principle be used to calculate the PMF. However it is well-known [12,13,14,15] that the exponential average in the Jarzynski equality depends crucially on a small fraction of realizations that transiently violate the second law of thermodynamics. Since such "magic" realizations are very unlikely to occur among a collection of fast rate realizations, it is clear that the potential of mean force cannot be determined accurately by the direct application of the Jarzynski equality.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate that the reconstructed free energy is an unbiased estimate of the underlying free energy and analytically derive an expression for the error. The present results can be applied to other history-dependent stochastic processes such as Wang-Landau sampling.In recent years increasing attention has been paid to the possibility of studying equilibrium thermodynamical processes by means of non-equilibrium processes [1,2,3,4,5]. A major breakthrough in this field is the work of Jarzynski [2] who has demonstrated that it is possible to estimate the free energy difference between two states as a suitable average of the work done on the system by forcing the transition in a finite time.…”
mentioning
confidence: 99%
“…a statistics that is both inherently noisy and biased, even if the spread of the work data is only moderately larger than k B T . [54][55][56][57][58] In case of Gaussian work distributions for the (forward) annihilation process, the Crooks theorem [40],…”
Section: Basic Theorymentioning
confidence: 99%